2023
DOI: 10.1021/acs.iecr.3c03668
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Adsorption Behavior and Mechanism of Pt(IV) and Pd(II) on Super Amino-Modified Monodispersed PGMA Microspheres

Fuchun Wang,
Wankun Wang,
Jianming Wu
et al.

Abstract: The present investigation described the application of high-capacity amino-group-functionalized polyglycidyl methacrylate monodispersed microspheres (PGMA-N) in the adsorption of Pt(IV) and Pd(II) ions from simulated wastewaters. The adsorption capacities of Pt(IV) and Pd(II) on PGMA-N were determined to be 3.93 and 4.99 mmol•g −1 , respectively, at 298 K and pH ∼ 4. These capacities are greater than those reported for other adsorbents in the literature. Rapid adsorption kinetics were observed for Pt(IV) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…PGMA microspheres have been investigated for their application in various fields, such as catalyst supports, , drugs, genes, and cell vectors, , and frameworks for complex architectures. , The application of PGMA microspheres as adsorbents for water treatment and removal and recovery of metal ions has been extensively studied. In these studies, PGMA microsphere structures were modified with various functional groups, such as ethylenediamine, diethylenetriamine, triethylenetetramine, , polyethylenimine, , iminodiacetic acid, aminoalkylcarboxylate, and aminoalkylphosphonic ligands . These investigations revealed that while certain metal ions, such as Co­(II), Cu­(II), Ni­(II), Hg­(II), Cd­(II), Au­(III), Pt­(IV), Pd­(II), Pb­(II), Zn­(II), and Nd­(III), form coordinate bonds with the PGMA surface, others, such as Cr­(VI) and As­(V), bind to the PGMA surface through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…PGMA microspheres have been investigated for their application in various fields, such as catalyst supports, , drugs, genes, and cell vectors, , and frameworks for complex architectures. , The application of PGMA microspheres as adsorbents for water treatment and removal and recovery of metal ions has been extensively studied. In these studies, PGMA microsphere structures were modified with various functional groups, such as ethylenediamine, diethylenetriamine, triethylenetetramine, , polyethylenimine, , iminodiacetic acid, aminoalkylcarboxylate, and aminoalkylphosphonic ligands . These investigations revealed that while certain metal ions, such as Co­(II), Cu­(II), Ni­(II), Hg­(II), Cd­(II), Au­(III), Pt­(IV), Pd­(II), Pb­(II), Zn­(II), and Nd­(III), form coordinate bonds with the PGMA surface, others, such as Cr­(VI) and As­(V), bind to the PGMA surface through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%